Nutrition Literacy Strategies for Improving Healthy and Nutritious Food Consumption Practices in Preschool Children - Purwanti, Rachma; Rizqiawan, Angga; Syahadah, Muti'ah Mustaqimatusy; Wijayanti, Hartanti Sandi; Margawati, Ani; Rahadiyanti, Ayu; Syauqy, Ahmad (Universitas Serang Raya, 2025)
Background: Food consumption practices in preschool children play a crucial role in shaping their dietary habits in later years. Effective nutrition literacy strategies are essential to foster healthy and nutritious food consumption among preschoolers. Aims: To identify problems, interviews were conducted with members of the kindergarten community, including teachers, parents, and students, and observations of the school environment. Methods: Community service with problem-based learning activities were conducted at At Tiin Kindergarten in Semarang City from July to September 2024. The participants in this initiative included 52 preschool children attending Class A at At Tiin Kindergarten. Participants were divided into two groups: a control group (Class A1) receiving a single storytelling session with story books and an intervention group (Class A2) receiving repeated storytelling sessions with story books. Results: The identified issues among the preschoolers included overnutrition (WHZ 17%; WAZ 7%; and BAZ 12%), undernutrition (WHZ 4%; WAZ 10%; BAZ 7%), and stunting (HAZ 4%). Following the implementation of storytelling and storybook-based interventions, children's nutritional literacy improved, especially in the intervention group (16 children), who participated in repeated storytelling sessions, compared to the control group (13 children), who only received one session. Conclusion: Repeated storytelling sessions led to greater gains in balanced nutrition knowledge and improved understanding of the MyPlate guidelines in preschool children. Suggestion: To further enhance nutritional literacy and promote balanced nutrition practices among preschool children, it is recommended that periodic activities be implemented to address and mitigate the issue of malnutrition in this age group.